Repression of MicroRNA‐30e by Hepatitis C Virus Enhances Fatty Acid Synthesis. Issue 7 (25th April 2019) - Sasaki, Reina; Sur, Subhayan; Cheng, Qi; Steele, Robert; Ray, Ratna B.
Abstract : Chronic hepatitis C virus (HCV) infection often leads to end‐stage liver disease, including hepatocellular carcinoma (HCC). We have previously observed reduced expression of microRNA‐30e (miR‐30e) in the liver tissues and sera of patients with HCV‐associated HCC, although biological functions remain unknown. In this study, we demonstrated that HCV infection of hepatocytes transcriptionally reduces miR‐30e expression by modulating CCAAT/enhancer binding protein β. In silico prediction suggests that autophagy‐related gene 5 (ATG5) is a direct target of miR‐30e. ATG5 is involved in autophagy biogenesis, and HCV infection in hepatocytes induces autophagy. We showed the presence of ATG5 in the miR‐30e–Argonaute 2 RNA‐induced silencing complex. Overexpression of miR‐30e in HCV‐infected hepatocytes inhibits autophagy activation. Subsequent studies suggested that ATG5 knockdown in Huh7.5 cells results in the remarkable inhibition of sterol regulatory element binding protein (SREBP)‐1c and fatty acid synthase (FASN) level. We also showed that overexpression of miR‐30e decreased lipid synthesis‐related protein SREBP‐1c and FASN in hepatocytes. Conclusion : We show new mechanistic insights into the interactions between autophagy and lipid synthesis through inhibition of miR‐30e in HCV‐infected hepatocytes. Abstract : HCV infection inhibited miR‐30e expression. Exogenous expression of miR‐30e targets ATG5 and inhibits HCV induced autophagy and lipid synthesis. These results provide new mechanistic insights into the interactions between autophagy and lipid synthesis via inhibition of miR‐30e in HCV infected hepatocytes.